Análise exploratória dos indicadores de resultado dos Núcleos de Apoio a Saúde da Família (NASF): a experiência de Belo Horizonte - Romilda Euzebio Araujo (2014)
The value of the assessment is increasing in relation to proposed institutions and programs in the new and complex contexts of contemporary society. In Brazil, the strengthening of assessment is noted from the 90s, with the proposition of public social policies that bring the expansion of citizen's rights, such as the Sistema Único de Saúde (SUS). The assessment is considered an important tool of health services, as it serves to support the planning and implementation of actions, guiding the efficient use of resources, measuring the quality and, also, the satisfaction of the population using the offered services. Among the many researchers in the field of health services quality assessment, the approach proposed by Avedis Donabedian has been accepted worldwide and is based on the analysis of the triad Structure, Process and Outcome. The recent creation of the Núcleo de Apoio à Saúde da Família (NASF), by the Health Ministry, points out the need for assessment of the performance of teams and results achieved for their support while policy. The purpose of this evaluative research was to analyze aspects of the triad Structure, Process and Outcome that permeate the operationalization of the services provided by the NASF and enable its operations in the city of Belo Horizonte. This studys sample was composed by two NASF and their respective teams, structured in two Centros de Saúde (CS) of different health districts. The data sources were records relating to the population served by the NASF, meeting records between NASF and ESF teams and interviews with managers of health centers, NASF and ESF professionals and users of the health service. The professionals from the NASF and ESF teams, the managers of both CS and users answered semi-structured questionnaires, which served as the base for the construction of the indicators that compose the triad. The results, discussed and interpreted, taking into account the studied context, showed weaknesses and interrelationships of the three aspects of the triad: the structural characteristics interfering in the process and its characteristics affecting the outcome. The use of Donabedians approach shown able to respond the purposes of this study, with the achievement of the objectives envisaged for the NASF hampered by the found weaknesses. It is hoped that the information gathered in this study may influence decisions made based on scientifically validated data and help develop strategies of political management, socially appropriate to strengthen the NASF together with the Primary Health Care.